2007
DOI: 10.1007/s00253-007-0934-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of twin-arginine (Tat)-dependent protein secretion of a heterologous model protein (GFP) in three different Gram-positive bacteria

Abstract: In contrast to the general protein secretion (Sec) system, the twin-arginine translocation (Tat) export pathway allows the translocation of proteins across the bacterial plasma membrane in a fully folded conformation. Due to this feature, the Tat pathway provides an attractive alternative to the secretory production of heterologous proteins via the Sec system. In this study, the potential for Tat-dependent heterologous protein secretion was compared in the three Gram-positive bacteria Staphylococcus carnosus, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
74
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(74 citation statements)
references
References 49 publications
0
74
0
Order By: Relevance
“…GFP was fused to the N terminus of YhcS to preserve the proper topology and avoid the secretion of GFP. GFP is not normally functional when translocated to the extracellular side of the membrane in bacteria (23,41).…”
mentioning
confidence: 99%
“…GFP was fused to the N terminus of YhcS to preserve the proper topology and avoid the secretion of GFP. GFP is not normally functional when translocated to the extracellular side of the membrane in bacteria (23,41).…”
mentioning
confidence: 99%
“…Recent metabolic engineering studies have shown that C. glutamicum is also capable of producing a variety of other commercially interesting compounds, e.g., other L-amino acids (4), D-amino acids (5), organic acids such as succinate (6)(7)(8)(9), diamines such as cadaverine (10,11) or putrescine (12), biofuels such as ethanol or isobutanol (13)(14)(15), and proteins (16)(17)(18).…”
mentioning
confidence: 99%
“…We also showed that pro-TG and pro-PG could be produced using the Tat pathway in C. glutamicum (20,21). More recently, Tat pathway-dependent secretion of GFP has been shown to be far more efficient in C. glutamicum than in two other gram-positive bacteria, B. subtilis and Staphylococcus carnosus (28), indicating that C. glutamicum could be a useful host for the production of heterologous proteins.…”
mentioning
confidence: 80%